Case report: Tissue positivity for SARS-CoV-2 in a preterm born infant death of thrombosis: possible intrauterine transmission - Greco, Salvatore; Sanz, Juana Maria; Bortolotti, Daria; Semprini, Chiara Marina; Braga, Carlotta; Gafà, Roberta; Santi, Erica; Maestri, Iva; Rizzo, Roberta; Greco, Pantaleo; Passaro, Angelina (Frontiers in Medicine, 2023)
Intrauterine transmission of SARS-CoV-2 (Severe Acute Respiratory Syndrome Corona Virus 2) is still matter of debate among scientists and there is limited information concerning this aspect of research. This could lead to severe complications of the growing fetus and, theoretically, of the newborn as well. We report the case of a male infant of 1,100 grams, born at 27th week of gestation to a SARS-CoV-2 mother, tested negative for viral detection at delivery. He was immediately admitted to neonatal Intensive Care Unit (ICU) for severe complications, where he died after 37 days by pulmonary embolism and thrombosis of the superior vena cava. After autopsy, SARS-CoV-2 N-protein and Spike RBD were detected in several tissues, particularly in the esophagus, stomach, spleen, and heart, with a significantly higher H-Score than the placenta. In conclusion, immunohistochemical analysis demonstrated SARS-CoV-2 NP and Spike RBD positivity in different tissues suggesting a possible intrauterine transmission. Newborn thrombo-embolism could be a complication of SARS-CoV2 infection as observed in adult patients.